Semi-closed reverse osmosis (SCRO): a concise, flexible, and energy-efficient desalination process - Mo, Zijing (2022)
As a promising solution to intensified water scarcity, desalination via membrane-based reverse osmosis (RO) attracts unprecedented interest in recent decades. However, the prevailing process, single-stage RO (SSRO), still consumes much higher than thermodynamic minimum energy as its operation requires over-pressurization (OP) of the feed. Although alternative RO processes, such as batch RO (BRO), closed-circuit RO (CCRO), and multiple-stage RO (MSRO), ameliorate OP, the mixing of recirculated concentrate and feed in BRO and CCRO generates entropy and increases energy consumption, while MSRO requires additional boosting systems that incur additional capital expenditures. Herein, we propose a new RO process with concise design and flexible operation, namely semi-closed reverse osmosis (SCRO). In SCRO, multiple-cycle operation with varied applied pressures is performed to mitigate OP without additional staging, while the intermediate feed and corresponding concentrate in each cycle are stored in separate tanks to circumvent mixing. Analytic results reveal that SCRO integrating energy recovery devices consumes similar energy to MSRO and less energy than all the other RO processes that have been tested at the bench- or pilot- scale for desalination within typical water recovery regions. Such superiority of SCRO is more significant at higher recoveries. This study suggests that SCRO can be a promising alternative to state-of-the-art RO processes in low-energy desalination.